Assessment of noise magnitude and velocity uncertainty in continuous GNSS coordinate time series - Mohammed, Ahmed (Advances in Geodesy and Geoinformation, 2024)
Global Navigation Satellite Systems (GNSS) technology has emerged as a powerful tool for unraveling Earth’s dynamic nature, offering continuous and precise monitoring of geodetic positions with global coverage. This study quantifies the noise magnitude and velocity uncertainty estimates using GNSS-derived coordinate time series data from 31 IGS global stations. It assessed the relationship between the noise level and the uncertainties related to the derived velocities and systematically evaluated the influence of different coordinate solution time spans, satellite orbit/clock products, and GNSS constellation on the noise level and velocity uncertainties. The result gives insights into GNSS velocity estimation, noise characteristics, and the influence of ambiguity resolution. The results suggested that resolving ambiguities and using specific GNSS constellation satellite orbits and clocks solutions enhances the precision of velocity estimates and reduces noise magnitude. The noise levels are observed to be consistently above –0.7 in 5-year solution sets and below –0.8 in 8-year solution sets. There is an average of 30 and 42% reduction in velocity uncertainties due to 3 year increment in solution span using JPL and ESA orbits, respectively. GPS-only solution set appeared to be favorable for high-precision GNSS-based geodynamic applications with increased favourability when the ambiguities are resolved. The identified noise model, GGM+WN, demonstrated the most appropriate noise model in most cases which is not out of place to have been used in quantifying the noise magnitude and velocity uncertainties in this study.